Microcrystalline Anthracene Enrichment-Spectrophotometry Determination of Trace Crystal Violet - Lu, Man; Zhan, Haihong; Li, Quanmin (Asian Journal of Chemistry, 2015)
A new method that utilizes microcrystalline anthracene as solid phase extractant was developed for the enrichment of trace crystal violet in water samples. It indicated that the crystal violet in water samples was completely surrounded by microcrystalline anthracene in the presence of NH4SCN and the microcrystalline anthracene carrier could be recycled after the desorption of crystal violet. Crystal violet could be detected directly by spectrophotometry under the maximum absorption wavelength (l = 579 nm). The influences of different parameters, such as the amount of NH4SCN and anthracene, acidity, enrichment time and coexistence of other salts on the enrichment yield of crystal violet have been studied to optimize the experimental conditions. The novel procedure was used to concentrate crystal violet in real water samples and the recovery is 62.4-103.1 %. Analytical results obtained by this novel method are very satisfactory.